Nanoscale Etching: Dissolution of III-As and Ge in HCl/H2O2 Solutions. (11th September 2015) - van Dorp, Dennis H.; Weinberger, David; Van Wonterghem, Simon; Arnauts, Sophia; Strubbe, Katrien; Holsteyns, Frank; De Gendt, Stefan
Abstract : In this work the etching kinetics of (100) III-As is studied at the nanoscale with ICP-MS for various HCl/H2 O2 mixtures. It is shown that the etch rate is controlled by both the concentration of the acid and the oxidizing agent. The surface termination during etching has strong impact on the etching kinetics. A similar effect was observed for Ge. The Ge (100) surface is sensitive to surface roughening during etching and reoxidation after native oxide removal.